Becoming-elemental – a thermal imaginary in the Anthropocene. (July 2022) - McHugh, Kevin
The Anthropocene problematic calls for imaginative aesthetic experiments fostering more-than-human thought and sensibilities. In this thought experiment, I draw on a sensing device in conjuring a thermal imaginary that decenters the human, espying a glimpse of a strange and uncanny world-without-us. The imaginary is a speculative performance in elemental attunement – becoming-molecular, becoming-imperceptible in the generative potentia of planetary heat – opening a pathway in rethinking bodies and worlds as emergent in, and through, forces elemental and cosmic in scope. The thermal imaginary accentuates the elemental as exorbitant, anonymous, and nonpossessable, an earthly plenum beyond any final capture, possession, mastery and control. Elemental alterity, the very strangeness of the earth, rises in the thermal imaginary as a summons, a calling from the "outside, " gesturing toward an immanent ethics of radical openness working in, and through, earthly bodies always already exposed and vulnerable in the force of the elemental. We must be open to the elemental summons, expanding capacities for what a body can do, moving beyond spinning reductive and redemptive Anthropocene narratives for saving this world. There can be no new bodies and worlds to come in the absence of an elemental ethics worthy of the earth itself.